Analisis Kesalahan Siswa dalam Menyelesaikan Soal Cerita Matematika pada Materi Barisan dan Deret Aritmatika - Nur, Nurfahmi; Rusli; Awi (Issues in Mathematics Education (IMED), 2018)
This study aims to describe the errors made by the students in solving mathematics word problems of arithmetic sequences and series. This research type is qualitative descriptive. Subject this research is students of SMA Negeri in Makassar grade XIth MIPA 4. Respondents of this research are selected based on the analysis of the test data observed from the error location based on polya steps as much as 3 students. The guidelines used to perform the analysis of types of errors are the troubleshooting Polya steps. Data collection techniques using the method of test and interview then through the three stages of data analysis, namely the condensation of data, presentation of data, and withdrawal conclusion. The results of the research obtained that in understanding the problem polya step the students do fact error type, in devising a plan polya step students doing the concept error type, in the step of polya carrying out the plan students perform the type of error operation and principle, in the step of polya looking back students do the kind of error principle. The results show that the errors that dominant students do that in the step of polya understanding the problem with this type of errors of fact and in the step of polya correcting back to the type of error principle. This is due to the ability of students in understanding the symbols on the row material and the arithmetic progression is still lacking, students are not accustomed to correcting back answers obtained, and students are not accustomed to write down the final conclusion.